Influence of Budget Participation, Decentralization Structure, and Public Accountability on Leadership Performance (An Empirical Study on the Leaders of Regional Work Units in Cirebon Regency) - Gustriani, Alva; Komara, Acep (Ann Publisher, 2024)
This study aims to analyze the effect of budget participation, decentralization structure and public accountability on leadership performance. The object in this study is the Regional Apparatus Work Unit (SKPD) of Cirebon Regency. The data used in this study are primary data. Data collection techniques by distributing questionnaires. The population in this study was 2 agencies and 10 agencies with a sample of 89 employees. The results of this study prove that: 1) Budget Participation affects the Performance of Leaders. 2) Decentralization Structure affects Leadership Performance. 3) Public Accountability affects the performance of the Leader. The data analysis used in this study was multiple linear regression using SPSS 25 for Windows Application.